STRATEGI AKSELERASI PEMASARAN DIGITAL PADA UMKM KACANG TOJEN DI KELURAHAN RENGAS PULAU DALAM MENGHADAPI PERSAINGAN PASAR MODERN - Ali Syah Putra (MTU PRESS, 2025)
The development of digital technology has transformed marketing patterns and business competition, including within the Micro, Small, and Medium Enterprises (MSMEs) sector. The Kacang Tojen MSME located in Rengas Pulau Village faces competitive challenges from modern market products that possess more structured distribution and promotional systems. This study aims to examine digital marketing acceleration strategies that can be implemented by MSMEs to enhance their competitiveness. The method employed in this research is a literature study by analyzing various journals and scientific references related to digital marketing, MSME strategies, and digital transformation. The findings indicate that the optimization of social media, the utilization of marketplaces, strengthening branding, and improving digital literacy are the primary strategies for accelerating the sustainable growth of MSME marketing.